Engineering Plant-Based Food Systems - Prakash Phd, Sangeeta; Prakash Phd, Sangeeta; Bhandari Phd, Bhesh; Gaiani, Claire (Academic Press, 2022)
Engineering Plant-Based Food Systems provides a comprehensive, in-depth understanding on the technologies used to create quality plant-based foods. This title helps researchers and food processors gain an understanding of the diverse aspects of plant-based foods, with a focus to meet the current consumers' demand of alternatives to animal products. This is a one-stop source that provides maximum information related to plant-based foods to food science researchers, food engineers and food processing/manufacturers. This book will enhance their understanding of plant-based protein sources, their application, product manufacturing, and bioavailability. In recent years, the emphasis on minimizing environmental footprints (climate change, greenhouse gas emissions, deforestation, and loss of biodiversity) and human health issues related to animal source food intakes has shifted the attention of researchers, dietitians and health professionals from animal-based diets to diets rich in plant-based foods (legumes, nuts, seeds). - Explores the plant sources available for extraction of proteins, the various extraction methods and the quality and functionality of the extracted proteins - Describes existing plant-based foods such as beverages, yogurts, spreads, fermented foods and meats - Provides information related to various plant based functional components such as polyphenols, phytosterols, aromatics and essential oils, etc.